Optimal battery energy storage system placement using whale optimization algorithm - Wong L.A.; Ramachandaramurthy V.K. (Warsaw University of Technology, 2023)
This paper proposes a technique to attain the optimal location of battery energy storage system (BESS) where the optimal solution is decided by using whale optimization algorithm (WOA). The objective function is formulated in order to minimize the total system losses in the distribution grid. Two cases are investigated in this paper where the first case focuses on the losses reduction in the conventional power grid while the second case involves a power grid with photovoltaic distributed generation (PVDG). The proposed technique has been applied on a generic distribution network and the results show that WOA can provide the optimal solution for BESS location in the distribution network, thus reducing the total system losses. 2020 Int. J. Elec. & Elecn. Eng. & Telcomm.